JAMINAN KONSTITUSIONALITAS ATAS KEBEBASAN BERAGAMA DAN BERKEYAKINAN - Prabowo, Hendro (Universitas Muhammadiyah Ponorogo, 2024)
This paper aims to provide an analytical comparison of the constitutions of Malaysia, the United States, Germany, and Indonesia, with a particular emphasis on the relationship between religion and belief as stated in their respective constitutional texts. The determination of the four countries above depends on a number of factors, including their legal systems, their level of development, the actors of a nation's attachment, and the state's secularism towards religion and belief. This writing uses a normative legal research method with a comparative approach and a legislative approach. Literature studies are used to collect legal materials and are carried out through searches in libraries and through the Internet. The interpretation method is used to analyze legal materials to understand the meaning of a statutory text. The findings of this study indicate that by establishing general and comprehensive guidelines regarding religion and belief in the Constitution of the Republic of Indonesia and maintaining impartiality towards all religions, Indonesia is sufficient to regulate religious and belief affairs within the framework of its constitution. Therefore, it is very important to implement legislative steps to foster a harmonious and peaceful religious life while eradicating the fundamental causes of blasphemy, as well as intolerance and discrimination in the context of religious beliefs and practices.